Women in Public Sphere after The Implementation of Islamic Sharia in Aceh - Sri Roviana; Wening Udasmoro; Euis Nurlaelawati (Al-Albab, 2021)
This article discusses several activities intended for Acehnese women after the implementation of Islamic sharia. Activities aimed at women in public spaces have an impact on the marginalization and narrowing of women's public spaces. This article also explicitly provides an overview and analysis of what actually happened to Acehnese women so that it appears that there is a problem of the domination of male power over women based on religious, cultural, and political arguments. The purpose of this article is for the public to understand that the Aceh government has made policies aimed at women in the public sphere with the support of Wilayatul Hisbah, which has an impact on the marginalization of women. It is found that after the implementation of Islamic law in 2001 until now, in Aceh, there have been domestication of women with various regulations (qonuns) as well as text interpretations which are used as legitimacy by the power of conservative ideology on progressive understanding. This article makes Aceh a focus area. This article is based on the literature as a secondary source as well as interviews with experts.